Optimization and Characterization of Mechanical Properties in Straw-Reinforced Cementitious Composites - Baohua Liu; Dongping Han; Fan Zhang; Junqi Zhang; Liang Fang (Buildings)
This study aimed to reduce the environmental impact of rapeseed straw accumulation and explore its engineering potential by examining how straw affects the mechanical properties of cement–sand composites. Experiments were conducted using varying straw dosages and curing ages to assess water consumption, setting time, flexural and compressive strengths, pore characteristics (via mercury intrusion), hydration products, and microstructures (via thermogravimetry and X-ray diffraction). Results showed that flexural and compressive strengths decreased with higher straw content, most notably up to 2%, but increased with age due to straw’s water absorption, which altered cement hydration and porosity. Over time, enhanced hydration and pore filling improved strength. This research supports straw’s use in civil engineering and advances eco-friendly concrete material development.